Primo Vascular System: Before the Past, Bizarre Present and Peek After the Future - Miroslav Stefanov (Medical Association of Pharmacopuncture Institute, 2022)
Introduction: Is Primo Vascular System (PVS) a paradox? Finding the connection between PVS as a carrier of information and the body's reactions at the micro and macro levels will be the starting point in understanding the meaning of life as such. Before the past of PVS knowledge: The initial phase of medicine in all cultures is reduced to the transfer of specific energy by special pathways throughout the body! This is the case in China, India, Japan, Korea, Tibet, etc. Undoubtedly, the five articles by B. H. Kim published in the early 1960s are considered to be the past of PVS. Strange present: PVS studies after 2002 are accepted as a present. Most of the articles on the topic are in journals with editors-in-chief originating and/or accepting the achievements of Eastern medicine. Is the science of PVS local since its research is in journals that publish mainly articles on Eastern medicine? Why few of the articles concerning PVS are in Western medicine journals? PVS: after the future or some conclusions and proposals: All substances, objects, biological objects generate a weak electromagnetic radiation typical for each of them which is a passport of the information. PVS has all the data to be the main carrier of information. Information medicine and Quantum Biology can serve as a basis for medicine and biomedical sciences, and it should explain the processes that exist for the change of DNA and organisms in